Rehabilitation of Older Adult Patients with Chronic Renal Failure on Dialysis Regimen - Sandra Nancy Méndez Rodríguez; Ibis Rodríguez Clavero (Revista Finlay)
Therapeutic physical exercise provides multiple benefits in patients with chronic kidney failure by reducing inflammatory mediators and increasing hemoglobin synthesis, nitric oxide bioavailability, antioxidant effects, hematocrit and muscle proteins and thus the number and size of the muscle fibers. Physical exercise has shown in kidney patients benefits at the cardiovascular, respiratory, and musculoskeletal levels, including a positive psychosocial effect. In addition, no serious complications or deaths related to physical exercise have been observed in these patients during dialysis.